ANALISIS KEBIJAKAN FISKAL DAN IMPLIKASINYA KEPADA PEREKONOMIAN INDONESIA: ANALISIS KESEIMBANGAN UMUM - Wawan Hermawan (Universitas Negeri Medan, 2016)
The economy cannot be separated from the role of government spending in stimulating the economy. Fiscal policy is government’s tool to intervene in theeconomy, could change for the better economy or even make the economy into a recession. On the other hand, economic activity over the impact of greenhouse gas contribution, so the impact on global climate change. Therefore, a certain sectorspecific fiscal policies have considerable impact in influencing greenhouse gases. This study aims to provide an analysis of fiscal policy scenarios that can affect greenhouse gases, so that could explain what sector-specific fiscal policies that can increase the risk of climate change. This research uses the model of Computable General Equilibrium (CGE) based fiscal policy held by the Ministry of Finance of the Republic of Indonesia named AGEFIS (Applied General Equilibrium Model for Fiscal). The scenario is to decrease fosil fuel subsidy that can produce CO2 emision. The results shows that decreasing fossil fuel subsidies can reduce the CO2 emission, but with high consequences. The consequences are the economic growth seen to fall, household wealth declined and the real consumption levels decrease.